Ta có: [tex]Q=\frac{2\sqrt{x}}{x-\sqrt{x}+1}> 0[/tex] (vì x > 0)
Lại có: [tex]Q=\frac{2\sqrt{x}}{x-\sqrt{x}+1}=2-\frac{2x-4\sqrt{x}+2}{x-\sqrt{x}+1}=2-\frac{2(\sqrt{x}-1)^2}{x-\sqrt{x}+1}\leq 2\Rightarrow 0\leq Q\leq 2[/tex]
Để Q nguyên thì [tex]Q\in \left \{ 1;2 \right \}[/tex]
+ [tex]Q=1\Leftrightarrow 2\sqrt{x}=x-\sqrt{x}+1\Leftrightarrow x-3\sqrt{x}+1=0\Leftrightarrow 3\sqrt{x}=x+1\Leftrightarrow 9x=x^2-2x+1\Leftrightarrow x^2-11x+1=0\Leftrightarrow x=\frac{11\pm 3\sqrt{13} }{2}[/tex]
+ [tex]Q=2\Leftrightarrow \frac{2\sqrt{x}}{x-\sqrt{x}+1}=2\Leftrightarrow \sqrt{x}=x-\sqrt{x}+1\Leftrightarrow x-2\sqrt{x}+1=0\Leftrightarrow (\sqrt{x}-1)^2=0\Leftrightarrow \sqrt{x}=1\Leftrightarrow x=1[/tex]